A novel colorimetric assay of β‐D‐glucans in basidiomycete strains by alcian blue dye in a 96‐well microtiter plate. (8th September 2015) - C. Semedo, Magda; Karmali, Amin; Fonseca, Luís
Abstract : Basidiomycete strains synthesize several types of β‐d ‐glucans, which play a major role in the medicinal properties of mushrooms. Therefore, the specific quantification of these β‐d ‐glucans in mushroom strains is of great biochemical importance. Because published assay methods for these β‐d ‐glucans present some disadvantages, a novel colorimetric assay method for β‐d ‐glucan with alcian blue dye was developed. The complex formation was detected by following the decrease in absorbance in the range of 620 nm and by hypsochromic shift from 620 to 606 nm (∼14 nm) in UV‐Vis spectrophotometer. Analysis of variance was used for optimization of the slope of the calibration curve by using the assay mixture containing 0.017% (w/v) alcian blue in 2% (v/v) acetic acid at pH 3.0. The high‐throughput colorimetric assay method on microtiter plates was used for quantification of β‐d ‐glucans in the range of 0–0.8 μg, with a slope of 44.15 × 10 −2 and a limit of detection of 0.017 μg/well. Recovery experiments were carried out by using a sample of Hericium erinaceus, which exhibited a recovery of 95.8% for β‐1, 3‐d ‐glucan. The present assay method exhibited a 10‐fold higher sensitivity and a 59‐fold lower limit of detection compared with the published method with congo red. β‐d ‐glucans of several mushrooms strains were isolated from fruiting bodies and mycelia, and they were quantified by this assay method. This assay method is fast, specific, simple, and it can be used to quantify β‐d ‐glucans from other biological sources. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:1526–1535, 2015